2004
DOI: 10.1111/j.1600-0870.2004.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

The intensification and shift of the annual North Atlantic Oscillation in a global warming scenario simulation

Abstract: The impact of global warming on the annual North Atlantic Oscillation (NAO) is investigated with a global warming scenario simulation of the ECHAM4/OPYC3 coupled general circulation model. It is shown that the annual meridional pressure gradient over the North Atlantic is significantly strengthened, and the two centers of action of the NAO, the Icelandic low and the Azores high, are intensified and shifted northeastward by 10° to 20° in latitude and 30° to 40° in longitude in the global warming scenario. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 42 publications
5
32
0
Order By: Relevance
“…The significant increase in mean NAOI value is consistent with previous climate change and MFR simulations (e.g. Karpechko, 2010;Gillet and Fyfe, 2013;Pausata et al, 2015), as is the eastward shift of the variability pattern (Hu and Wu, 2004;Kuzmina et al, 2005;Dong et al, 2011;Pausata et al, 2015) which has itself been linked to a more positive NAO (Peterson et al, 2003). Even though the differences in the location of the NACs across different climate models can be very large (Davini and Cagnazzo, 2014), the eastward shift of the two poles under anthropogenic climate change scenarios therefore appears to be a robust result.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The significant increase in mean NAOI value is consistent with previous climate change and MFR simulations (e.g. Karpechko, 2010;Gillet and Fyfe, 2013;Pausata et al, 2015), as is the eastward shift of the variability pattern (Hu and Wu, 2004;Kuzmina et al, 2005;Dong et al, 2011;Pausata et al, 2015) which has itself been linked to a more positive NAO (Peterson et al, 2003). Even though the differences in the location of the NACs across different climate models can be very large (Davini and Cagnazzo, 2014), the eastward shift of the two poles under anthropogenic climate change scenarios therefore appears to be a robust result.…”
Section: Discussionsupporting
confidence: 77%
“…A number of modelling studies suggest a future positive shift in the NAO as part of anthropogenic climate change (e.g. Hu and Wu, 2004;Kuzmina et al, 2005;Karpechko, 2010;Gillet and Fyfe, 2013). The changing weather patterns associated with a more positive NAO will likely affect PM concentrations across Europe, with potentially major impacts on public health (Pausata et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Peterson et al (2003 have suggested that this shift is simply a consequence of the trend towards a more positive NAO index in the last two decades of the 20th century. Hu and Wu (2004), using both data and a coupled general circulation model, have also shown that a shift of both SLP centres of action took place in the second half of the last century, which will likely continue in the future. Our study confirms that this shift also occurs under a global warming scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Gillett and Fyfe, 2013;Karpechko, 2010;Stephenson et al, 2006;Kuzmina, 2005;Hu and Wu, 2004); however, the driving mechanisms behind these shifts are still under debate. Hori et al (2007) have shown that NAO variability does not change substantially in the SRES-A1B scenarios compared to the 20th century, and conclude that the trend in the NAO index is the result of an anthropogenic trend in the basic mean state, rather than being due to changes in NAO variability.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the Mediterranean region is projected to have less cyclonic and more anticyclonic activity until the end of the 21st century (Hueging et al, 2013;Kjellström et al, 2011). The Icelandic Low and Azores High are projected to be shifted northeastward in the global warming scenario revealed by GCM studies (e.g., Hu & Wu, 2004;Reyers et al 2015), and the intensification of the pressure gradient between the main centers (i.e., the Azores High and Icelandic Low) over the North Atlantic have been identified (Hu & Wu, 2004;Knippertz et al, 2000). The northward displacement of zonal winds could lead to more frequent windstorms over the North Sea (Hueging et al, 2013;Pinto et al, 2007).…”
Section: Projected Changes In Large-scale Pressure Conditions Over Eumentioning
confidence: 99%